Cationic starch for microalgae and total phosphorus removal from wastewater. Issue 4 (27th May 2013) - Anthony, Renil; Sims, Ronald
ABSTRACT The city of Logan, Utah treats wastewater in 460 acres of facultative lagoons. Naturally growing algae in these lagoons uptake nutrients and remediate the wastewater, but require coagulation and flocculation for separation from wastewater. Cationic corn starch and cationic potato starch with a degree of substitution 1.34 and 0.82, respectively, were synthesized using 3‐methacryloyl amino propyl trimethyl ammonium chloride and tested on Scenedesmus obliquus and lagoon wastewater. The zeta potential of the cationic starches tested over a pH range 5.0–10.0 showed an average of +16.0 and +15.1 mV for cationic corn starch and cationic potato starch, respectively. Total suspended solids removals of 90 and 85% were achieved with cationic corn starch and cationic potato starch, respectively, when tested with S. obliquus. Tests with wastewater showed total suspended solids removals of 80 and 60% for cationic corn starch and cationic potato starch, respectively. Total phosphorus removal values from wastewater were approximately 33, 29, and 42% for cationic corn starch, cationic potato starch, and alum, respectively, for a coagulant/algae ratio of 1.4 (wt/wt). These results indicate that cationic starch has the potential to replace alum for algae harvesting and wastewater treatment making it a suitable alternative to inorganic coagulants and flocculants. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2572–2578, 2013